The honeymoon effect : the science of creating heaven on earth - Lipton, Bruce H. (Hay House, Inc., 2013)
The honeymoon effect : a state of bliss, passion, energy and health resulting from a huge love. Your life is so beautiful that you can't wait to get up to start a new day and you thank the Universe that you are alive. In his new book, Bruce H. Lipton, PhD, asks readers to think back on the most spectacular love affair of their lives -- the Big One that toppled them head over heels. It was a time when they were exuberantly healthy, when they were overflowing with energy, when they were loving their lives so much they couldn't wait to bound out of bed in the morning to experience more. It was the 'honeymoon effect' that was to last forever. Lipton explains that this 'honeymoon effect' was not a chance event but a personal creation. Just as important, he explains why honeymoons are so often short lived. This book describes how readers manifested the honeymoon effect and the reasons they lost it in their lives. That knowledge empowers them to create the honeymoon again, this time in a way that ensures a happily-ever-after relationship that even a Hollywood producer would love.